A supporting service differentiation multichannel MAC protocol for wireless ad hoc networks. (19th February 2008) - Zhiyan, Cao; Zhenzhou, Ji; Mingzeng, Hu
Providing service differentiation by using distributed control at the MAC layer is an effective mechanism for supporting Quality of Service (QoS) in wireless ad hoc networks. However, existing QoS-capable MAC protocols have been designed in single channel environments. Multichannel technology has been demonstrated to significantly increase network capacity, reduce chances of contention and collision of data transmission. So, QoS guarantee is easier to achieve by using multichannel technology. In this paper, we devise a supporting service differentiation multichannel MAC protocol. Two interfaces are used, an interface staying at common control channel is responsible for assigning data channel and another can dynamically switch channel for data transmission. In the common control channel, different priority flows adopt different backoff parameters to access channel to acquire data channel assignment chance. Simulation results show the protocol outperforms Enhanced Distributed Coordination Function (EDCF) of IEEE 802.11e.